Effect of local radiofrequency hyperthermia on the intratumoral pressure and extracellular matrix stiffness in hepatocellular carcinoma - Anna Bottiglieri; Poonam Yadav; Santosh K. Mandal; Malea Williams; Amanda McWatters; Rahul A. Sheth; Punit Prakash (International Journal of Hyperthermia)
Background Increased intratumoral pressure and stiffening of the extracellular matrix are biophysical barriers to effective drug delivery in hepatocellular carcinoma (HCC). Local thermal interventions alter these biophysical characteristics of the tumor.Purpose To characterize time-dependent and thermal dose-related effects of radiofrequency hyperthermic (RFHT) interventions on intratumoral pressure and tumor stiffness.Methods Two treatment protocols (high input power > 1 W and low input power < 1 W) were investigated using a computational modeling approach and a syngeneic rat HCC tumor model with a customized monopolar RFHT system. Intratumoral pressure and stiffness were assessed using piezo-electric sensors and ultrasound shear wave elastography (SWE), respectively, across three groups (untreated tumors, tumors treated with high and low RFHT) and time points (immediately after treatment, at 24 h, and 48 h).Results The developed RFHT system maintained electrode-tip temperatures of 74.1 ± 5.2 °C (high RFHT) and 45.9 ± 1.6 °C (low RFHT) for 15 min. Histological analysis confirmed larger necrotic areas in the high RFHT group compared with low RFHT (p < 0.01) and control groups (p < 0.001). The initial intratumoral hypertension significantly decreased in both treated groups at 24 h and 48 h (p < 0.01 high RFHT, p < 0.05 low RFHT). Tumor stiffness significantly decreased (p < 0.05) only in the low RFHT group at the end of treatment. This change was spatially-dependent within the tumor and a recovery toward initial conditions was observed at 48 h (p < 0.01).Conclusions Local RFHT induces time- and heating profile-dependent alterations in intratumoral pressure and stiffness in a rat model of HCC, suggesting that RFHT interventions may modulate tumor biophysics and influence drug delivery.